Pengaruh Kualitas Pelayanan Dan Customer Experience Terhadap Kepuasan Konsumen Di Iky Salon Waioti - Tobi, Maria Fatima Edo; Rangga, Yoseph Darius Purnama; Tokan, Maria Goreti Mao (Jurnal Projemen UNIPA, 2026)
This study aims to analyze the effect of service quality and customer experience on consumer satisfaction at Iky Salon Waioti. This research employs a quantitative approach using primary data collected through questionnaires distributed to 100 respondents. The data were analyzed using validity and reliability tests, classical assumption tests, multiple linear regression analysis, as well as t-tests and F-tests. The results indicate that service quality has a positive and significant effect on consumer satisfaction. Customer experience also has a positive and significant effect on consumer satisfaction. Simultaneously, both variables significantly influence consumer satisfaction. These findings suggest that improving service quality and creating positive customer experiences are important factors in enhancing consumer satisfaction and strengthening the competitiveness of Iky Salon Waioti.